Back to Bismarck? Shifting preferences for intragenerational redistribution in OECD pension systems - Tim Krieger; Stefan Traub (Luxembourg Income Study (LIS), 2008)
Using a sample of 20 OECD countries it is shown that the majority of countries decreased the level of intragenerational redistribution in the first pillar of their pension systems, though the evidence is weak in statistical terms. We find strong correlations between changes of the so-called Bismarckian factor and changes of the generosity of the pension system, the shape of the income distribution in terms of its first three central moments and life expectancy. An economic laboratory experiment confirms that these variables could have been causal for the observed change.
Keywords: H55; D71; J18; D63; C92; 330; earnings-related and flat-rate benefits; Beveridge vs. Bismarck; pension reform; relative deprivation; OECD countries; experiments; Gesetzliche Rentenversicherung; Rentenfinanzierung; Einkommensumverteilung; OECD-Staaten; Test; Theorie